Médecine et sexualité, aperçus sur une rencontre historiographique (Recherches francophones, époques moderne et contemporaine) - Chaperon, Sylvie; Hanafi, Nahema (Clio. Femmes, Genre, Histoire, 2013)
Cet article rappelle dans quelles circonstances une histoire de la sexualité construite à partir de sources médicales a émergé en France dans les années 1970. Il insiste surtout sur les pionnier-e-s de cette histoire pour les périodes moderne et contemporaine et les sources qu’ils et elles ont utilisées. Enfin il met en avant le renouvellement récent de ce champ grâce à une histoire « par en bas ».
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; justice sociale; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques